CYP1A2 is expressed along with CYP1A1 in the human lung - Wei, Cindy; Cacavale, Robert J.; Kehoe, John J.; Thomas, Paul E.; Iba, Michael M. (Cancer letters, 2001)
The expression and activity of CYP1A1 were examined in fresh, small-sized lung biopsy specimens from nine human subjects. CYP1A1 transcripts were detected by reverse transcription-polymerase chain reaction (RT-PCR) analysis of total lung RNA. CYP1A2 transcripts were detected in the RNA samples as well, and bioactivation of 2-aminofluorene (2-AF) or 2-amino-3,4-dimethylimidazo[4,5-f]quinoline (MeIQ), a CYP1A2-preferential activity, was catalyzed by the lung S 9 fractions also. Two major bands were detected in the whole homogenate by western blot analysis using CD3, a mouse anti rat CYP1A1 monoclonal that cross-reacts with rat CYP1A2 as well as with human CYP1A1 and CYP1A2. S 9 fractions from the tissues catalyzed the bioactivation of benzo[ a]pyrene (B[ a]P), a CYP1A1-preferential activity, to mutagens in the Ames assay. Our findings are in agreement with the known presence of CYP1A1 in the human lung, and provide strong evidence for the expression of catalytically functional CYP1A2 in the tissue.